REFLECTIVE PRACTICE-ORIENTED ONLINE DISCUSSIONS: A NARRATIVE STUDY ON EFL STUDENT-TEACHERS DURING COVID-19 PANDEMIC - Astuti, Widi; -, Dwiniasih; Budiana, Haris (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
During the COVID-19 pandemic, teaching and learning activities have been shifted to online learning. Therefore, online discussion activities were carried out to achieve learning objectives. The transition of learning methods was expected to be able to replace face-to-face teaching and learning activities in schools. This research aimed to find out the reflection on the problems and how to solve the problems in online discussion activities by EFL Student-Teachers. The method used in this research is qualitative with narrative as the research design. Providing a questionnaire and interview that must be answered by EFL Student-Teachers. The participants of this research were 26 EFL Student-Teachers from one of the University in Cirebon who have carried out PLP II activities. The results of this research indicated that online discussion activities required good media and preparation for teaching and learning activities. EFL Student-Teachers were required to be creative in carried online discussion activities to get students' attention, and EFL Student-Teachers must be able to solve the problem faced during the online discussion as the reflection of teaching and learning activities. Keywords: Reflective Practice, Online Discussion, EFL Student-Teachers, COVID-19.